Rituximab is highly effective for pure red cell aplasia and post-transplant lymphoproliferative disorder after unrelated hematopoietic stem cell transplantation - Kopińska, Anna; Helbig, Grzegorz; Frankiewicz, Andrzej; Grygoruk-Wiśniowska, Iwona; Kyrcz-Krzemień, Sławomira (Contemporary Oncology/Współczesna Onkologia, 2012)
Pure red cell aplasia (PRCA) and post-transplant lymphoproliferative disorder (PTLD) constitute rare complications after allogeneic hematopoietic stem cell transplantation (AlloHSCT). The incidence of EBV-PTLD is above 1%, but it may increase in patients with well-known risk factors such as EBV seronegativity at the time of transplantation, T-cell depletion of donor grafts, HLA mismatch and use of antithymocyte globulin (ATG) for prophylaxis of graft versus host disease. The risk factors for PRCA were defined and they include: 1) elevated post-transplant anti-donor isohemagglutinin titers, 2) reduced-in- tensity conditioning before transplant, 3) the presence of anti-A agglutinin and 4) ciclosporin for graft versus host disease (GVHD) prophylaxis and 5) transplant from sibling donor. The anti-CD20 monoclonal antibody rituximab remains the first line treatment for PTLD following AlloHSCT, but its efficacy in PRCA is limited. Reduction of immunosuppression is also strongly advised. This is the first report on an adult patient who simultaneously developed PRCA and PTLD after ABO-mismatched AlloHSCT. The early introduction of rituximab resulted in prompt resolution of clinical symptoms with subsequent full recovery.